THE KYIV MERIDIAN AXIAL CIRCLE’ OBSERVATIONAL ARCHIVE AS THE UKRVO SCIENTIFIC RESOURCE - Zolotukhina, A. (Одеські астрономічні публікації, 2013)
We describe the database of CCD- observations conducted withMeridian Axial Circlein 2001-2003. Inthat time it was equipped with a ISD017AP CCD having 1040x1160 pxs, 16 mkm pixel size and 1.394" per pixel scale.which is the component of UkrVO astro-information resource. We developed the software for management and accumulation of these and new data, which will be used to create a catalogue for clarification of coordinates of faint stars. We note that the MAC is a refractor (D=180 mm, F=2.3 m) which is used now in a CCD astrometric survey of the equatorial zone.